Super Partes? Assessing the Effect of Judicial Independence on Entry - Conti, Raffaele; Valentini, Giovanni (Management Science, 2018)
Incumbents can enjoy a cost advantage vis-à-vis new entrants and so deter new firm entry by establishing and leveraging connections with the judicial system. Connected firms may in fact avoid fully complying with the costly norms implied by a law, a regulation, or a contract. At the same time, they can also credibly threaten to sue new entrants. Therefore, a change in the institutional environment that diminishes the ability of incumbent firms to establish judicial connections—i.e., an increase in judicial independence—can promote entrepreneurship. Exploiting reforms that change the way in which U.S. state judges are selected, we confirm that this is the case, and we show that this effect is more salient in states and industries where the likelihood of entering into a business dispute is higher. The paper also sheds some light on the mechanisms behind this effect. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2794 . This paper was accepted by Toby Stuart, entrepreneurship and innovation.